PERANCANGAN SISTEM INFORMASI PENJUALAN PADA TOKO SARI COLLECTION BERBASIS WEBSITE - Razi, Fahrul (ITB Ahmad Dahlan Jakarta, 2024)
With the development of internet technology, one of the most affordable forms of communication networks with an infinite receiving range is now possible. The development of information and communications technology, particularly in the area of e-commerce, has an impact on the business sector. The idea of online purchasing and selling of commodities is known as e-commerce. The issue that frequently arises in the case study of Toko Sari Collection is represented by offline promotions, manual data processing, and offline-only sales systems. The goal of this research is to build information systems based on e-commerce in order to address current issues. The findings and recommendations of this research are presented in the form of e-commerce sales websites that have the potential to increase sales volume and streamline data processing and promotion procedures.